Synonymy of Katianna coeruleocephala Handschin, 1920 (Collembola: Katiannidae) with Bourletiella viridescens (Bourletiellidae) - Greenslade, Penelope (Zootaxa, 2016)
Katianna coeruleocephala was described by Handschin in 1920 from Poespo, Java. It was collected in December, 1896 by Dr. Zehntner with the collecting details given as rotten “Louv” (leaves?) from live orchard. Handschin (1920) labelled his figures of the species (p. 146) as Katianna coerulescephala but the first spelling of the species name (p. 145) has priority. Katianna coeruleocephala has never been recollected. The only mention of the species in the literature since 1920 has been by Suhardjono (1989) in a check list for Indonesia and Suhardjono (2012) who listed it as present on Java and provided the main characteristics of the genus Katianna Börner, 1923. She stated it was a “new” (translate as endemic?) species in Java with a preferred habitat in cold and damp litter but no comment was made on the taxonomic status of the Indonesian species.